Judicial Role Conflict in Civil Dispute Resolution in Indonesia: Judges as Adjudicators and Mediators at the Religious Court of Curup - M.Reivaldy Elfitra Samudra Tungga; Syarial Dedi; Ilda Hayati; Rifanto bin Ridwan (Berasan: Journal of Islamic Civil Law, 2025)
The expansion of judicial functions through court-annexed mediation has led judges to serve not only as adjudicators but also as mediators in the resolution of civil disputes. This situation gives rise to potential role conflicts that have implications for the principles of judicial impartiality and independence. This study aims to analyze the forms and dynamics of judges’ role conflicts in practice, as well as their implications for the implementation of court-annexed mediation in Indonesia. This study employs an empirical legal approach through a case study at the Curup Religious Court, utilizing case file analysis and interviews with judge-mediators. The findings reveal that role conflict is a tangible phenomenon experienced by judges, particularly when performing mediation functions and subsequently adjudicating the same case. Nevertheless, this conflict does not directly undermine judicial impartiality, as it is addressed through the internalization of professional ethics and a commitment to independence. However, these findings also reveal that the effectiveness of judicial mediation remains highly dependent on the individual integrity of judges and is not yet fully supported by an optimal institutional design. This study contributes theoretically by positioning judges’ role conflict as an inherent characteristic managed within a hybrid dispute resolution system, and by emphasizing the importance of an approach that considers the interaction between norms, structures, and actors in the development of court-annexed mediation in Indonesia as part of a global issue.